Productivity of land agricultural innovation in the low countries (1250-1800) (Leuven University Press, 1978)
Publ. simultaneously in the series of the Belgisch Centrum voor Landelijke Geschiedenis, Centre Belge d'histoire rurale ; 55. - Index. - ISBN 90-6186-073-3.